Anatomical and radiographic assessment of variations of the mental foramen and their impact on success of local anaesthesia administration - Jannat, Isratul; Ummay Salma, M.; Chowdhury, Nipu Rani; Nahar, Kulsum; Mostafa, Dilruba Binte; Emon, Khandokar Emanuzzaman; Sarmin, Shahela (International Journal of Research in Medical Sciences, 2026)
Background: Successful local anesthesia in dental practice relies heavily on precise knowledge of mandibular anatomical landmarks, particularly the mental foramen. Variations in the position, shape and number of the mental foramen may contribute to anesthetic failure and neurovascular complications during dental procedures. Understanding these variations is therefore essential for improving clinical outcomes. Methods: This descriptive cross-sectional study was conducted in the Department of Dentistry at Rangpur Medical College Dental Unit from March 2024 to February 2025. A total of 120 patients undergoing mandibular radiographic evaluation for diagnostic or treatment purposes were included using a convenient sampling technique. Digital panoramic radiographs were assessed bilaterally, resulting in evaluation of 240 mandibular sides. Results: The majority of patients were aged 26–35 years (35.8%), with a slight male predominance (55.8%). The mental foramen was most commonly located between the first and second premolars (42.1%), followed by a position below the second premolar (40.4%). Oval-shaped mental foramina were most frequent (54.6%), while irregular shapes were rare. A single mental foramen was observed in 90.8% of patients, whereas accessory mental foramina were present in 9.2%. Bilateral symmetry was noted in 64.2% of cases, while 35.8% showed asymmetry, often requiring modification of local anesthetic techniques. Conclusion: Anatomical variations of the mental foramen are common and clinically significant. Routine radiographic evaluation can enhance the accuracy of local anesthetic administration and reduce the risk of anesthetic failure and nerve-related complications.